2006
DOI: 10.1128/jvi.02551-05
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Functional Characterization of the Equine Herpesvirus 1 DNA Polymerase and Its Accessory Subunit

Abstract: We report the expression and characterization of the putative catalytic subunit (pORF30) and accessory protein (pORF18) of equine herpesvirus 1 DNA polymerase, which are encoded by open reading frames 30 and 18 and are homologous to herpes simplex virus type 1 UL30 and UL42, respectively. In vitro transcriptiontranslation of open reading frames 30 and 18 generated proteins of 136 and 45 kDa, respectively. In vitroexpressed pORF30 possessed basal DNA polymerase activity that was stimulated by pORF18, as measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…As is the case in all herpesviruses studied to date, an accessory protein, EHV-1 pORF18, which stimulates nucleotide incorporation by Pol, forms the viral DNA polymerase holoenzyme together with the catalytic subunit [20]. Thus, we compared DNA polymerase activities of Pol D752 and Pol N752 in the absence or presence of pORF18 under different assay conditions (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…As is the case in all herpesviruses studied to date, an accessory protein, EHV-1 pORF18, which stimulates nucleotide incorporation by Pol, forms the viral DNA polymerase holoenzyme together with the catalytic subunit [20]. Thus, we compared DNA polymerase activities of Pol D752 and Pol N752 in the absence or presence of pORF18 under different assay conditions (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…The pol subunit is known to perform the synthesis of leading and lagging strands, while the PAP tethers the holoenzyme to the DNA, thus conferring processivity [65,66,67]. Since the replication of all known herpesviruses takes place in the host cell nucleus [68], these high molecular weight proteins need to be actively transported through the NPC to reach the site of viral DNA replication.…”
Section: Dna Polymerase Holoenzyme Nuclear Transportmentioning
confidence: 99%
“…These differences occurred mostly as single nucleotide polymorphisms (SNPs), causing coding changes in 31 ORFs, although the significance of these substitutions has been proved only in the case of a few ORFs, of which the two most important are ORF30 and ORF68. The SNPs in ORF30 could be associated with the neuropathogenic attributes of virus strains (Loregian et al, 2006;Nugent et al, 2006;Goodman et al, 2007), although in some cases the non-neuropathogenic genotype was found to be the causative agent in a disease with neurological signs (Heerkens, 2009). In a previous study a primer-probe energy transfer method was developed for the differentiation of neuropathogenic and non-neuropathogenic genotypes of EHV-1 strains.…”
mentioning
confidence: 99%